Transnational policy discourses on 'teacher quality': An educational connoisseurship and criticism approach. Issue 3 (April 2019) - Nordin, Andreas; Wahlström, Ninni
In this article, we analyse key policy documents on teacher quality produced by the OECD and the EU during the period 2005 to 2017 using an educational connoisseurship and criticism approach. The purpose of this article is to explore how Eisner's concepts of educational connoisseurship and educational criticism can be understood and used to analyse educational policy, especially how teacher quality is discursively constructed in transnational authoritative texts on education policy. Eisner's three aspects of criticism, description, interpretation and evaluation can be utilised in a differentiated critical approach to the analysis of transnational policy documents on education. While the critical descriptive discourse can be viewed as 'identifying a simple relationship' between social development and educational needs, the interpretative critical discourse can be regarded as 'recognising the complexity' of teachers' tasks in changing societies and the critical evaluative discourse as 'recognising and problematising contradictory interests' that affect teachers' work. We argue that the philosophical concepts of connoisseurship and criticism contribute to policy research by demonstrating that a multifaceted concept of teacher quality is needed to capture the complex nature of education.